Navigating the limits: electoral management bodies and the struggle against disinformation and foreign interference - Parenteau Ian (Filozofija i Društvo, 2025)
The problem of disinformation and foreign interference in elections has increased significantly in recent years. It creates an uneven playing field that hinders fair competition and informed voting. Electoral disinformation manifests itself in two ways: partisan and procedural. Partisan disinformation targets candidates and voters with false information to influence their voting preferences. In contrast, procedural disinformation seeks to disenfranchise voters or undermine the electoral process. Foreign interference in elections can be defined as any attempt to influence the outcome of an election in another country. Have Electoral Management Bodies (EMBs) implemented effective countermeasures to mitigate these risks? The answer is complex, but no. They face institutional, legal and technical constraints that limit their actions. First, EMBs cannot change electoral laws to make them more resilient against the threat of disinformation and foreign electoral interference. Second, disinformation is usually not criminal and falls outside most legislation, making prosecution difficult. Foreign interference falls beyond national jurisdiction. Third, the actions that EMBs can take are limited by their obligations to be fair and impartial. Fourth, while enhancing content curation on social media platforms would be beneficial, EMBs lack the authority to enforce such measures, and these platforms exercise limited control over the content that is published.